Mid-Term frequency domain scheduler for resource allocation in wireless mobile communications systems. (2017)
This article approaches the dynamic resource allocation problem for the downlink of a wireless mobile communication system (WMCS). The article defines the architecture and functions of the global resource scheduler, as well as the quality index for scheduling, the signal to interference-plus-noise ratio (SINR). The proposed approach divides the scheduling task into two components: a distributed one, with local, short-term scope; and a centralized one, with global, medium-term scope. The optimization model considers a set of slack variables for guaranteeing feasibility. This allows the service provider to fully satisfy the users' service demands. The model type is mixed, non-linear, which demands large computational power for an exact solution. So an approximate strategy is used, in order to decouple the search space.